Inflammatory Activity on Natalizumab Predicts Short-term but not Long-term Disability in Multiple Sclerosis - Raffel,J; Gafson,AR; Dahdaleh,S; Malik,O; Jones,B; nicholas,R (PLOS One, 2017)
BACKGROUND: In people with multiple sclerosis treated with interferon-beta or glatiramer acetate, new MRI lesions and relapses during the first year of treatment predict a poor prognosis. OBJECTIVE: To study this association in those receiving natalizumab. METHODS: Data were collected on relapses, new MRI activity, and Modified Rio Score after initiation of natalizumab in an observational cohort of 161 patients with high baseline disability. These were correlated with Expanded Disability Status Scale (EDSS) progression at years 1, 2, 3, and 3-7 after treatment initiation, versus pre-treatment baseline. RESULTS: 46/161 patients had a relapse in the first year and 44/161 had EDSS progression by year 2. Relapses and Modified Rio Score in the first year of treatment predicted EDSS progression at year 1 and 2 after treatment initiation. However, this effect disappeared with longer follow-up. Paradoxically, there was a trend towards inflammatory activity on treatment (first year Modified Rio Score, relapses, and MRI activity) predicting a lower risk of EDSS progression by years 3-7, although this did not reach statistical significance. Those with and without EDSS progression did not differ in baseline age, EDSS, or pre-treatment relapse rate. Relapses in year 0-1 predicted further relapses in years 1-3. CONCLUSIONS: Breakthrough inflammatory activity after natalizumab treatment is predictive of short-term outcome measures of relapses or EDSS progression, but does not predict longer term EDSS progression, in this cohort with high baseline disability.